Relationship between Household Food Insecurity and Toddler Health - Rizqia Diningtyas, Mayang; Widyawati, Diah (Riviera Publishing, 2023)
Food insecurity is a global issue and its alleviation is stipulated in the 2030 SDGs target 2.1, namely zero hunger and achieving food security for all people. Food insecurity can affect health physically, mentally, socially, and quality of life directly or indirectly due to malnutrition. This study aims to identify the relationship between the level of food insecurity and the health of children under five using an order logit regression model from the March 2021 Susenas data. This study used March 2021 Susenas data from the Central Bureau of Statistics (BPS). The data used in this study is cross-sectional data at the individual level. The results show that food insecurity, according to the level of severity, is statistically significant and positively related to children's health complaints. Immunization as an important control variable is also statistically significant and positively related to toddler health complaints. Based on the food insecurity level, the order logit regression analysis results prove that food insecurity is significant and has a positive effect on health complaints. Food insecurity occurs not only in low-income household groups but also in high-income household groups.